2015
DOI: 10.21767/2254-6081.100020
|View full text |Cite
|
Sign up to set email alerts
|

Zonisamide: Antiproliferative and Antioxidant Effects on C6 Glioma Cancer Cell Model

Abstract: Seizures are often seen in patients with brain tumors and antiepileptic drugs such as acetazolamide, valproic acid. Some of these antiepileptic drugs also have anti-cancer effects that have been shown in many studies. For instance, valproic acid has been shown to be related to apoptosis pathway and induced the suppression of C6 glioma cell migration. Zonisamide is also commonly used as an antiepileptic drug because of its scavenging effects on hydroxyl and nitric oxide radicals. Due to valproic acid's anticanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…As far as we know, there are no major pre-clinical or clinical studies focusing on the effects of zonisamide in brain tumors. One experimental study has demonstrated that zonisamide has antiproliferative effects in C6 rat glioma cells [ 86 ].…”
Section: Use Of Ca Inhibitors In Brain Tumorsmentioning
confidence: 99%
“…As far as we know, there are no major pre-clinical or clinical studies focusing on the effects of zonisamide in brain tumors. One experimental study has demonstrated that zonisamide has antiproliferative effects in C6 rat glioma cells [ 86 ].…”
Section: Use Of Ca Inhibitors In Brain Tumorsmentioning
confidence: 99%